October 16, 1943/Eight Jews - Debenedetti, Giacomo, 1901-1967 (Book collections on Project MUSE., 2001)
"For more than fifty years, Giacomo Debenedetti's October 16, 1943 has been considered one of the best and most accurate accounts of the shockingly brief and efficient roundup of more than one thousand Roman Jews from the oldest Jewish community in Europe for the gas chambers of Auschwitz. Completed a year after the event, Debenedetti's intimate details and vivid glimpses into the lives of the victims are especially poignant because Debenedetti himself was there to witness the event, which forced him and his entire family into hiding." "Eight Jews, the companion piece to October 16, 1945, was written in response to testimony about the Ardeatine Cave Massacres of March 24, 1944. In this essay, Debenedetti offers insights into that grisly horror and into assumptions about racial equality. Both of these stunning works are appearing together, along with Alberto Moravia's preface to Debenedetti's October 16, 1943, for the first time in an American translation. October 16, 1943/Eight Jews gives American readers a first glimpse into the extraordinary mind of the man who was Italy's foremost critic of twentieth-century literature."--Jacket